2021
DOI: 10.51298/vmj.v506i1-2.972
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Complication at Both Receiving and Donor Sites in Facial Autologous Fat Transfer

Abstract: Autologous fat grafting is a technique that has been used for a long time in the field of plastic surgery. Besides many advantages, the complications, which can range from mild such as hematoma, infection, calcification, necrosis... even death is a big problem.  The article presents a case of using autologous fat taken from the abdomen to graft onto the facial area with complications of severe infection in both the receiving and donor sites, causing necrosis of fat and skin in both areas. The treatment takes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…In the literature studies conducted, which examines the relationship between capital structure and financial performance "Güneysu, Atasel and Şeker (2021), Ngoc,Tien and Thu (2021); Le and Phan, 2017;; ; ; Salim and Yadav (2012); by " found a negative relationship between capital structure and ROA and ROE. While in the mentioned studies, the relationship between capital structure and financial performance was examined, in this study, the effect of cost of debt on financial performance was examined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature studies conducted, which examines the relationship between capital structure and financial performance "Güneysu, Atasel and Şeker (2021), Ngoc,Tien and Thu (2021); Le and Phan, 2017;; ; ; Salim and Yadav (2012); by " found a negative relationship between capital structure and ROA and ROE. While in the mentioned studies, the relationship between capital structure and financial performance was examined, in this study, the effect of cost of debt on financial performance was examined.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of evaluating the literature as a whole, it was determined that regression analysis was used in the studies. Some of the studies examining the effect of capital structure, debt financing and debt structure on financial performance include positive results that are " Baraklı and Öndeş (2021); ; ; Muchugia (2013); Nirajini and Priya (2013); " and some studies including " Say and Doğan (2022); ; Ngoc,Tien and Thu (2021); Ophelia et al (2021); Çanakçıoğlu and Ersan (2020); Özdemir (2019); ; Le and Phan (2017); ; ; ; ; Salim and Yadav (2012); " were obtained negative results. In some studies, " ; Obert and Olawale (2010) it was found that capital structure; debt financing and debt structure do not have a significant effect on financial performance.…”
Section: Literature On Researchmentioning
confidence: 99%